Evaluation of antioxidant and antimicrobial activities of Oligomeris linifolia (Vahl) J.F. Macbr. - Khan, Muhammad Nadeem; Khan, Muhammad Wasim; Khan, Rahmat Ali (Bangladesh Journal of Botany, 2019)
Fine powder of Oligomeris linifolia was extracted with 70% methanol. Crude Oligomeris linifolia methanol extract (OLME) were assessed for antioxidant, antibacterial and antifungal characteristics. All the tested OLME showed potent antioxidant, antibacterial, and antifungal activities. The results clearly showed that Oligomeris linifolia methanol extracts is a source of potential therapeutic compounds against antibacterial, antifungal and free radical associated disorders.